2022
DOI: 10.1080/21655979.2021.2024336
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Eukaryotic translation initiation factor 3D induces stem cell-like properties and metastasis in cervix cancer by activating FAK through inhibiting degradation of GRP78

Abstract: Cervix cancer (CC) is the most common gynecological malignancy and the leading cause of morbidity among women worldwide. Previous study indicated that cancer stem cells (CSCs) existed in cervix cancer, and suppressing CSC characteristics of cervix cancer is needed to combat this disease. Eukaryotic translation initiation factor 3 (EIF3) is one of the most complex eukaryotic translation initiation factors containing 13 subunits (EIF3A-EIF3M) and it regulates eukaryotic translation. One member of EIF3, EIF3D, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Knocking down EIF3D can inhibit the proliferation and invasion of breast cancer cells by inhibiting the activation of the Wnt/β-catenin signal pathway [69]. Overexpression of EIF3D induces stem cell-like characteristics and metastasis in cervical cancer cells by inhibiting GRP78 degradation and activating FAK [70]. EIF1 is a 12kDa protein that plays many important roles in translation initiation in eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…Knocking down EIF3D can inhibit the proliferation and invasion of breast cancer cells by inhibiting the activation of the Wnt/β-catenin signal pathway [69]. Overexpression of EIF3D induces stem cell-like characteristics and metastasis in cervical cancer cells by inhibiting GRP78 degradation and activating FAK [70]. EIF1 is a 12kDa protein that plays many important roles in translation initiation in eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…EIF3D is a subunit of EIF3 that facilitates the cap-dependent translation of approximately 20% of mRNA ( de la Parra et al, 2018 ). EIF3D was widely studied in cancer and was known to promote the progression of cervical cancer ( Zhong and Lan, 2022 , 78), gallbladder cancer ( Zhang et al, 2017 ), and renal cell carcinoma ( Pan et al, 2016 ; Huang et al, 2019 ). Besides, EIF3D might serve as an independent poor prognostic marker in lung adenocarcinoma ( Wang et al, 2019 )…”
Section: Discussionmentioning
confidence: 99%
“…Morphological abnormalities and unlimited proliferation are common hallmarks of tumor cells ( 52 , 53 ). Examination of human cancer tissues has revealed that eIF3d expression is upregulated in many cancers including cancers of breast ( 54 ), prostate ( 55 ), ovary ( 56 ), gallbladder ( 21 ), stomach ( 57 ), bladder ( 58 ), colon ( 59 ), lung ( 60 ), and cervix ( 61 ) as well as in glioma ( 62 ), renal cell carcinoma ( 63 ), and chronic hepatitis C–associated hepatocellular carcinoma ( 64 ). These findings suggest that eIF3d may associate with tumorigenesis or cancer cell proliferation.…”
Section: Eif3d In Pathology and Diseasementioning
confidence: 99%
“…5 C ). First, ectopic overexpression of eIF3d significantly promoted the proliferation, migration, and stem cell–like properties of cervical cancer cells via activating the glucose-regulated protein 78 (GRP78)–focal adhesion kinase pathway ( 61 ). Similar findings have been made with ectopic eIF3d overexpression in colon cancer cells in which increased cell proliferation was observed as determined using colony formation, MTT, and soft-agar assays ( 59 ).…”
Section: Eif3d In Pathology and Diseasementioning
confidence: 99%